Evaluation and treatment of Langerhans cell histiocytosis patients with central nervous system abnormalities: Current views and new vistas. Issue 1 (25th September 2017) - Yeh, E. Ann; Greenberg, Jay; Abla, Oussama; Longoni, Giulia; Diamond, Eli; Hermiston, Michelle; Tran, Brandon; Rodriguez‐Galindo, Carlos; Allen, Carl E.; McClain, Kenneth L.; ,
Abstract: Central nervous system (CNS) involvement in Langerhans cell histiocytosis (LCH) can include mass lesions of the hypothalamic pituitary axis, choroid plexus, cerebrum, and cerebellum or magnetic resonance imaging (MRI) signal abnormalities of the cerebellum, pons, and basal ganglia. The term neurodegenerative (ND) CNS‐LCH has been given to the MRI signal abnormalities and neurologic dysfunction, although initially patients may have no clinical symptoms. Standardized evaluations to better understand the natural history and response to therapy are needed. We propose guidelines for clinical, radiologic, and physiologic tests as a framework for developing the best methods of evaluation, which can then be tested in prospective treatment protocols.